The Desicion Making of Transformasional Leadership: Pengambilan Keputusan Kepemimpinan Transformasional - Wati, Ainul Fidia; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to describe and prove women's leadership in decision making in the Food and Agriculture Office of Sidoarjo Regency. The research method used is correlational quantitative. The sampling technique used is simple random sampling. Determination of the number of samples using the Tarro Yamane formula with a total of 166 respondents. The results of this study prove that there is an influence of women's leadership on decision making either partially or simultaneously in the Food and Agriculture Office of Sidoarjo Regency. Women's leadership which includes idealized influence (X1), inspirational motivation (X2). Intellectual stimulation (X3), and individualized consideration (X4) have a simultaneous effect on decision making (Y) at the Food and Agriculture Office of Sidoarjo Regency. In addition, the idealized influence variable (X1) partially has a significant effect on decision making (Y). Inspirational motivation (X2) has no significant effect on decision making (Y). Intellectual stimulation (X3) has a significant effect on decision making (Y). And the individualized consideration variable (X4) has a partial effect on decision making (Y).